Case Report: Safety and Efficacy of Denosumab in Four Children With Noonan Syndrome With Multiple Giant Cell Lesions of the Jaw - Ferriero, Kristen; Shah, Biraj; Yan, Yun; Khatri, Surya; Caccamese, John; Napoli, Joseph A.; Bober, Michael B.; Crane, Janet L. (Frontiers in Pediatrics, 2020)
Noonan syndrome is a genetic disorder caused by mutations in the RAS/MAPK pathway. Multiple giant cell lesions are a rare sequelae of disruptions in this pathway, termed Noonan-like multiple giant cell lesions (NL/MGCLs). Medical management of these tumors rather than surgical intervention is preferential as the lesions are benign but locally destructive and recurring. This case series describes four male pediatric patients with Noonan syndrome and multiple giant cell lesions of the jaw treated with denosumab, a monoclonal antibody to receptor activator of nuclear factor kappa B ligand (RANKL), which has been approved for the treatment of malignant giant cell tumors in adults but not evaluated for safety or efficacy in children. All four pediatric patients responded clinically and radiographically to the treatment. Adverse events occurred in a predictable pattern and included hypocalcemia and joint pain during the initiation of treatment and symptomatic hypercalcemia after the cessation of treatment. Growth was not significantly impaired in these skeletally immature patients. This case series demonstrates how a weight-adjusted denosumab dose can effectively treat NL/MGCLs and provides laboratory data for consideration of the timing of monitoring for known side effects.